Disclosure of HIV status outcome of regular counseling in a cohort of patients attending HIV clinics - Ssali, Livingstone; Wasagami, Francis; Kateeba, Agnes; Nantume, Sophie; Kiboneka, Andrew (Retrovirology, 2012)
The African continent bears the greatest burden of HIV/AIDS in the world. Efforts by scientists to find a vaccine for curing the pandemic have proved futile to date. The prevalence in Uganda stands at 6.4%in Adults and 0.7 % in Children, and about 1.1 million Ugandans are living with HIV/AIDS. The AIDS Support Organization started in 1987. Non disclosure of HIV sero status affects uptake of HIV/AIDS health services, increases stigma and discrimination.
Keywords: Peer Support Group; Counseling Service; Voluntary Counselling; Disclosure Status